Physical activity in the prevention of peripheral artery disease in the elderly - Schiattarella, Gabriele G.; Perrino, Cinzia; Magliulo, Fabio; Carbone, Andreina; Bruno, Antonio G.; De Paulis, Michele; Sorropago, Antonio; Corrado, Roberto V.; Bottino, Roberta; Menafra, Giovanni; Abete, Raffaele; Toscano, Evelina; et al. (Frontiers in Physiology, 2014)
Aging is a well-known cardiovascular risk factor and cardiovascular diseases (CVD) are estimated to be the most common cause of death in the elderly. Peripheral arterial disease (PAD) represents an important clinical manifestation of CVD leading to increase morbidity and mortality, especially in elderly population. The correct management of PAD population includes the prevention of cardiovascular events and relief of symptoms, most commonly intermittent claudication. Progressive physical activity is an effective treatment to improve walking distance and to reduce mortality and cardiovascular events in patients with PAD, however the ability to effectively engage in physical activity often declines with increasing age. The maintenance and increase of reserve functional capacity are important concepts in the elderly population. Ultimately, the goal in participation of physical activity in the healthy elderly population is maintenance and development of physical functional reserve capacity. Therefore, for individuals suffering of PAD, appropriate physical activity in the form of supervised exercise may serve as a primary therapy. Although there are few direct comparisons of therapeutic exercise programs versus pharmacological or surgical interventions, these increases in walking distance are greater than those reported for the most widely used agents for claudication, pentoxyphylline and cilostazol. Despite a reduction in mortality and improvement of quality of life caused by physical activity in the PAD population, the molecular, cellular, and functional changes that occur during physical activity are not completely understood. Therefore, this review paper aims at presenting an overview of recent established clinical and molecular findings addressing the role of physical activity on PAD in the older population.